The reflections of a continued training proposal in the teacher's speech that exercise teaching with students classes (Research, Society and Development, 2018)
This study aimed to verify the reflections about a proposal of continued education in the speech of teachers who work with included students. The sample was composed by 14 Elemantary School teachers, from the public education system in Alegrete/RS. Data collect was executed in 2017. The tools in this data collect were questionnaires, reflexive conversation circles and short courses with specialized professionals, who considered about historical and legal aspects and about the importance of adapting the curriculum to consolidate school inclusion. After the proposition about education, the teachers understood that the way is to search theoretical deepening about the theme, showing comprehension about how fundamental it is to plan and to use methodologies that help the disabled student to understand the studied topics in class. Therefore, the belief is that the biggest contribution from this study was to evidence, through reflections and redeterminations, the importance of continued education to the execution of teaching for disabled students.